A self-verification temperature sensor based on surface plasmon resonance in a hollow core negative curvature fiber. (2nd June 2022) - Chen, Qiang; Chen, Hailiang; Liu, Yundong; Wang, Yujun; Fan, Xiaoya; Bai, Ge; Zhang, Mengwei; Du, Huijing
Abstract: We proposed and simulated a surface plasmon resonance (SPR) temperature sensor with two loss peaks in a hollow core negative curvature fiber (HC-NCF). Inner walls of the anti-resonant tubes in HC-NCF were plated with gold films to stimulate SPR, while the thermo-optic mixture of toluene and chloroform was filled in the air holes in HC-NCF to modulate the coupling between core modes and surface plasmon polaron modes (SPPMs). Simulation results showed that two SPPMs with opposite thermo-optic respond effects were excited at two separate wavelength bands due to their different dispersion characteristics. Temperature measurement sensitivities of −3.976 nm °C −1 and 1.071 nm °C −1 were obtained for the two SPPMs, while the sensitivity reached −5.047 nm °C −1 when detected the wavelength interval between the two SPPMs loss peaks. The two separate loss peaks could also be utilized in self-verification. The designed temperature sensor based on HC-NCF and SPR depicts high sensitivity and self-verification, which could be utilized for high precision and stable temperature monitoring.